Servant Leadership, Organizational Culture and Organizational Citizenship Behavior on Innovative Work Behavior - Baety, Nur; Rojuaniah, Rojuaniah (Universitas Negeri Semarang, 2022)
This study aims to identify the relationship between servant leadership and organizational culture with innovative work behavior through organizational citizenship behavior . This research was conducted through a survey of 179 employees at one of the consumer goods industrial companies in Bekasi, Indonesia in November 2021, who had worked for more than one year from staff to management positions, by distributing questions electronically. The Smart PLS structural equation model is used to analyze the data. The results of the analysis show that servant leadership and organizational culture had positive effect on organizational citizenship behavior, servant leadership has an indirect relationship in increasing innovative work behavior, organizational culture and organizational citizenship behavior had positive effect to increase innovative work behavior in consumer goods industry employees. It is hoped that this research can be used as a reference in developing further research on the influence of servant leadership and organizational culture to increase innovative work behavior through organizational citizenship behavior and can be used as a consideration in implementing effective human resources.